Biologically active indole and bisindole alkaloids from Tabernaemontana divaricata - Kam, Toh-Seok; Pang, Huey-Shen; Lim, Tuck-Meng (2003)
The ethanol extract of the leaves of Tabernaemontana divaricata (double flower variety) provided a total of 23 alkaloids, including the new aspidosperma alkaloids, taberhanine, voafinine, N-methylvoafinine, voafinidine, voalenine and the new bisindole alkaloid, conophyllinine in addition to the previously known, biologically active bisindole, conophylline and its congener, conofoline. The structures of the new alkaloids were established by spectroscopic methods. The preparation and characterization of the corresponding quinones of the biologically active bisindoles are also described in relation to a structure-activity study of these compounds with respect to their action in stimulating insulin expression.